(untitled) (International Journal of Engineering Management Science, 2022)
An effective control method, including system-level control and pulse width modulation for quasi-Z source cascade multilevel inverter (qZS-CMI) based grid-tie photovoltaic (PV) power system is proposed. The system-level control achieves the grid-tie current injection, independent maximum power point tracking (MPPT) for separate PV panels, and dc-link voltage balance for all quasi-Z-source H-bridge inverter (qZS-HBI) modules. The first solution comprises a full-SiC two-level QZS inverter, while the second design was built based on a three-level neutral-point-clamped QZS inverter with Silicon based Metal–Oxide–Semiconductor Field-Effect Transistors (Si MOSFETs). Several criteria were taken into consideration: the size of passive elements, thermal design and size of heatsinks, voltage stress across semiconductors, and efficiency investigation. The Photovoltaic (PV)-string rated at 1.8 kW power was selected as a case study system. The advantages and drawbacks of both solutions are presented along with conclusions.